1999
DOI: 10.1139/cjm-45-3-257
|View full text |Cite
|
Sign up to set email alerts
|

Fate of <i>Cryptosporidium</i> oocysts, <i>Giardia </i>cysts, and microbial indicators during wastewater treatment and anaerobic sludge digestion

Abstract: The extent of reduction in selected microorganisms was tested during both aerobic wastewater treatment and anaerobic digestion of sludge at the wastewater treatment plant in Ottawa to compare the removal of two encysted pathogenic protozoa with that of microbial indicators. Samples collected included the raw wastewater, the primary effluent, the treated wastewater, the mixed sludge, the decanted liquor, and the cake. All of the raw sewage samples were positive for Cryptosporidium oocysts and Giardia cysts, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
55
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 0 publications
8
55
0
1
Order By: Relevance
“…Because most of the human-virulent microsporidian spores identified in the present study were viable, we conclude that environmental contamination derived from landfill leachates and sewage sludge represents both serious public and veterinary threats particularly in the light of the massive amounts of sewage sludge utilized by agriculture or deposited in landfills (Sobsey 1978;Chauret et al 1999;Yangin et al 2002;Szostakowska et al 2004;Westrell et al 2004;Hutchison et al 2005), the environmental robustness of spores (Didier et al 2004;Matchis et al 2005), and their high virulence to humans Weiss 2001). Also, the previous identification of E. intestinalis spores in groundwater indicates that these spores can be transported in the subsurface media (Dowd et al 1998).…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Because most of the human-virulent microsporidian spores identified in the present study were viable, we conclude that environmental contamination derived from landfill leachates and sewage sludge represents both serious public and veterinary threats particularly in the light of the massive amounts of sewage sludge utilized by agriculture or deposited in landfills (Sobsey 1978;Chauret et al 1999;Yangin et al 2002;Szostakowska et al 2004;Westrell et al 2004;Hutchison et al 2005), the environmental robustness of spores (Didier et al 2004;Matchis et al 2005), and their high virulence to humans Weiss 2001). Also, the previous identification of E. intestinalis spores in groundwater indicates that these spores can be transported in the subsurface media (Dowd et al 1998).…”
Section: Discussionmentioning
confidence: 64%
“…Environmental pollution with anthropozoonotic enteropathogens is no longer a local problem but has become a global concern because the use of sewage sludge on agricultural and livestock grazing lands or deposition in landfills can cause serious environmental, public health, and veterinary consequences in developed and developing countries (Sobsey 1978;Straub et al 1993;Chauret et al 1999;Yangin et al 2002;Szostakowska et al 2004;Westrell et al 2004;Hutchison et al 2005). For the sewage sludge end products to be used without restriction on agricultural lands to grow ready-to-eat crops, the pathogen load must be reduced to a level, which does not pose or poses acceptable public health or veterinary risks (Straub et al 1993;Yangin et al 2002;Westrell et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aerobic spores, clostridial spores, particles have been evaluated on a limited scale as surrogates for protozoa presence (Rose et al, 1988;LeChevallier et al, 1991;Payment and Franco, 1993;Hijnen, 1997;Chauret et al, 1999). In a previous study (Bonadonna et al, 2002b) performed on water samples collected in a municipal sewage treatment plant, the results, through a probing statistical analysis, showed that none of the selected microrganisms was a reliable predictor of the presence of the parasite, whereas a significant correlation with pH, redox potential and total organic carbon was instead calculated.…”
Section: Discussionmentioning
confidence: 99%